Services Bestowed by The Academic Libraries During Covid-19 Outbreak: A Thematic Analysis - Noryana Binti Ahmad Khusaini; Nordibradini Binti Selamat (Universitas Airlangga, 2024)
Background: Academic libraries are important information agencies that are established to support teaching, learning, and research activities at universities. It is a leading information organization that is important to the sustainable development of universities and providing versatile human capital of one country. As far as we are concerned, due to the pandemic, universities are still operating and are transforming their operation into 360 degrees using online platforms. Due to that, academic libraries all around the globe spare no effort to ensure they are still operating during the pandemic to support online teaching and learning classes. All efforts they took were documented and shared throughout journal publication. This research was carried out to get a bird's-eye view from many librarians and researchers around the globe. Methods: Document analysis and thematic analysis methods were used in this study. Purpose: This study aims to identify the services offered by academic libraries worldwide during the COVID-19 pandemic. Findings: As for the findings of services, the themes associated with it were identified. It includes digital library services, virtual references, webinars, services with health protocol and regulation, social media, combating fake news, collaboration with publishers, document delivery services, special project support teaching and learning, and research endeavors. Conclusion: Academic libraries should endeavor to provide their services to the public, regardless of the circumstances, as long as they remain under human control. Keywords: Academic Library Services, COVID-19, Thematic Analysis. ————————————————————————————————————- ABSTRAK Layanan Perpustakaan Perguruan Tinggi Selama Wabah Covid-19: Analisis Tematik Latar Belakang: Perpustakaan akademik merupakan lembaga informasi penting yang didirikan untuk mendukung kegiatan belajar mengajar, dan penelitian di universitas. Perpustakaan akademik merupakan organisasi informasi terkemuka yang penting bagi pembangunan berkelanjutan universitas dan penyediaan sumber daya manusia yang serba guna di suatu negara. Sejauh yang kami ketahui, karena pandemi, universitas masih beroperasi dan mengubah operasinya menjadi 360 derajat menggunakan platform daring. Oleh karena itu, perpustakaan akademik di seluruh dunia tidak menyia-nyiakan upaya untuk memastikan bahwa mereka masih beroperasi selama pandemi untuk mendukung kelas belajar mengajar daring. Semua upaya yang mereka lakukan didokumentasikan dan dibagikan melalui publikasi jurnal. Penelitian ini dilakukan untuk mendapatkan pandangan menyeluruh dari banyak pustakawan dan peneliti di seluruh dunia. Metode: Analisis dokumen dan metode analisis tematik digunakan dalam penelitian ini. Tujuan: Penelitian ini bertujuan untuk mengidentifikasi layanan yang ditawarkan oleh perpustakaan akademik di seluruh dunia selama pandemi COVID-19. Temuan: Mengenai temuan layanan, tema yang terkait dengannya diidentifikasi. Layanan yang disediakan meliputi layanan perpustakaan digital, referensi virtual, webinar, layanan dengan protokol dan regulasi kesehatan, media sosial, penanggulangan berita bohong, kerja sama dengan penerbit, layanan pengiriman dokumen, dukungan proyek khusus untuk pengajaran dan pembelajaran, serta kegiatan penelitian. Kesimpulan: Perpustakaan akademik harus berupaya memberikan layanan kepada masyarakat, apa pun keadaannya, selama layanan tersebut tetap berada di bawah kendali manusia. Kata Kunci: Layanan Perpustakaan Akademik, COVID-19, Analisis Tematik.